2021
DOI: 10.3390/pr9091546
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Characterization of Acoustic Cavitation Bubbles with Respect to the Bubble Size Distribution at Equilibrium

Abstract: In addition to bubble number density, bubble size distribution is an important population parameter governing the activity of acoustic cavitation bubbles. In the present paper, an iterative numerical method for equilibrium size distribution is proposed and combined to a model for bubble counting, in order to approach the number density within a population of acoustic cavitation bubbles of inhomogeneous sizing, hence the sonochemical activity of the inhomogeneous population based on discretization into homogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…Ultrasonic frequency is an important physical parameter of the sono-chemical reaction that can significantly affect the size of cavitation bubbles. It is found that as the frequency increases, the cavitation temperature and pressure can be increased; when the ultrasonic frequency increases to a certain level, the size and lifetime of the cavitation bubbles decrease, which weakens the cavitation intensity and thus reduces the efficiency of the photocatalytic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonic frequency is an important physical parameter of the sono-chemical reaction that can significantly affect the size of cavitation bubbles. It is found that as the frequency increases, the cavitation temperature and pressure can be increased; when the ultrasonic frequency increases to a certain level, the size and lifetime of the cavitation bubbles decrease, which weakens the cavitation intensity and thus reduces the efficiency of the photocatalytic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, at variance from the setup commonly used in sonoluminescence experiments, our samples do not include dissolved gas species. In this simpler context, the more complicated models give the same answer as the original Rayleigh–Plesset equation, then, we will only consider the RP model in our discussion. …”
Section: Introductionmentioning
confidence: 99%
“…In this simpler context, the more complicated models give the same answer as the original Rayleigh–Plesset equation, then, we will only consider the RP model in our discussion. 52 57 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, the sonochemical process of generation of free radicals [14] , [15] , degradation of organic contaminants [16] , [17] , or even production of hydrogen [18] , [19] , [20] has been elucidated through chemical mechanisms associated to the thermodynamics of the oscillation of the single acoustic cavitation bubble. The population dimension has been also integrated in the modelling of sonochemistry [21] , [22] , through the number density of bubbles [23] , [24] and their size distribution [25] . On the other hand, the physical effects associated with the oscillation of the single acoustic cavitation bubble have been studied via mathematical modelling and simulation in a number of scientific papers dealing with microjets [26] , shockwaves [27] , acoustic streaming [28] and microstreaming [29] .…”
Section: Introductionmentioning
confidence: 99%